Evaluation Criteria for Appropriate Site and Environmental Development in Green Building Implementation of Hospital Facilities in Palu City - Fritswel Ratmady P; Tutang M. Kamaludin; Gunawan; Zet Mallisa; Bayu Rahmat Ramadhan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research is expected to be able to see to what extent this building has implemented the green building concept by conducting an assessment according to green building criteria in the Appropriate Site and Environmental category. This research uses a mixed research method between quantitative research methods and qualitative research methods. This research will comprehensively measure and analyze aspects of Appropriate Site and Environmental Use in Hospital Buildings in Palu City, after that disseminate the findings in the field. After obtaining information regarding the general description of the green building system from the results of interviews with each respondent from the three hospitals involved. reviewed. Thus, the result of reducing the data that has been collected is an interview sheet in the form of a table of more specific questions based on the Greenship Existing Building Version 1.1 assessment benchmark and the Greenship New Building Version 1.2 assessment benchmark. Based on the results of the appropriate site and environmental assessment (Appropriate Site Development), Anutapura Hospital and Undata Hospital received a gold title with a score of 9 points or (57%) of the maximum total points of 16, while Tadulako University Hospital received a silver title with the lowest score. 9 points or (52%) of the maximum total points of 17.